Awareness, use and perception of patient versions of clinical practice guidelines - a national cross-sectional survey among patients with a cancer diagnosis and healthcare providers - S. Blödt; S. Erstling; M. Becker; G. Carl; M. Follmann; S. Frenz; C. Holmberg; T. Langer; A. Pachanov; D. Pieper; M. Nothacker (BMC, 2024)
Abstract Background To investigate awareness, use, and perceptions of the patient guidelines (PGs) of the German Guideline Program in Oncology (GGPO) and to explore general preferences regarding cancer information among patients and healthcare providers (HCPs). Methods Two cross-sectional surveys among patients with cancer (November 2020-May 2021) and among HCPs (April -June 2021) were set up as anonymised, self-administered, semi-structured online surveys, including open-ended questions. Data were analysed with descriptive statistics and qualitative thematic analysis. Patients were recruited from national self-help organisations and certified cancer centres located all over Germany. HCPs were recruited from cancer centres, scientific medical societies and guideline groups. Results Of 816 participating patients, 45% were aware of the GGPO-PGs, while 55% of the 455 participating HCPs were aware of them. Of those aware of the GGPO-PGs, 65% of patients and 86% of HCPs perceived them as helpful, while 95% in both groups saw them as comprehensive. Seventy-five percent of patients and 85% of HCPs were satisfied with the GGPO-PGs, 22%/13% were partially satisfied, and 3%/2% were rather/not at all satisfied. In addition to self-help organisations, physicians and hospitals were perceived as central in distributing the GGPO-PGs. More patients (78%) than HCPs (56%) stated a preference for detailed information, although the wish for concise information - e.g. decision aids - was concurrently expressed by the majority of all participants. Thematic analysis showed that up-to-dateness, trustworthiness, and supportive messaging are important properties for PGs. Conclusions HCPs found the GGPO-PGs helpful, but awareness was low, which suggests that dissemination should be improved. This is also true for patients; however, further research needs to be done to increase the helpfulness of PGs for patients. Oncological PGs seem to be needed in different formats according to patients' situational needs. Theory-driven research should investigate how to best frame patient information in a supportive way.